Image Processing with Virtual Pencil and Virtual Mouse using Webcam Recognition for Drawing - Rikip Ginanjar; Sijoatmodjo Ivan Carnelius (President University, 2016)
Recently, people use physical mouse to control the computer. Virtual Vpaint can be a new innovation to change the physical mouse to virtual mouse, then the users can minimize the cost of hardware consumption and damages. Having virtual mouse, users can control the computer only through webcam to do a lot of things such as drawing, editing images, mouse control, and others. Virtual VPaint application will discuss the development of Computer Vision for drawing an object in Windows form application by using virtual mouse. This application can perform common image editor such as blurring, gray scaling, and negating images. Users can control mouse pointer through the webcam by using object mover which has specific color, then can draw an object on canvas by using virtual pencil.